2004
DOI: 10.1136/jnnp.2003.026013
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal derived cerebrospinal fluid proteins in different forms of dementia: is a meningopathy involved in normal pressure hydrocephalus?

Abstract: Objectives: In animal models and in vitro studies leptomeninges have been shown to be the origin of neurotrophic substances that support the survival and growth of neuronal cells. Because dementia is associated with neuronal loss, we investigated whether leptomeningeal dysfunction may be involved in the pathogenesis of dementia disorders. Methods: We analysed the cerebrospinal fluid (CSF) concentrations of the leptomeningeal derived b trace protein, b2 microglobulin, and cystatin C.Results: There was a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Additionally, lipocalin-type prostaglandin D synthase (PGDS), also known as b-trace protein, considered to be mainly produced in the leptomeninges playing a role in prostaglandin metabolism and in retinoids’ transfer, has been found to have significantly lower concentration in CSF of NPH patients than in patients with other causes of dementia, such as AD, patients with depression and healthy individuals [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, lipocalin-type prostaglandin D synthase (PGDS), also known as b-trace protein, considered to be mainly produced in the leptomeninges playing a role in prostaglandin metabolism and in retinoids’ transfer, has been found to have significantly lower concentration in CSF of NPH patients than in patients with other causes of dementia, such as AD, patients with depression and healthy individuals [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that while the models used in our study suggest diagnostic value of the novel biomarkers, other combinations of these markers may be optimal; it will be of interest in future studies to validate the results of this discovery study in additional cohorts and to determine whether alternative combinations of these markers may demonstrate improved performance. The levels of at least 7 of the novel biomarkers have been evaluated in AD subjects in other studies: no change was observed in plasma PAI-1 levels [44] ; in agreement with our findings, two studies have reported increased CSF MIF in AD and MCI subjects [45] , [46] ; also consistent with our findings, increased fibrinogen levels have been observed in AD and MCI CSF [47] and in AD plasma [48] , and increased plasma levels have been associated with an increased risk of future dementia [49] ; results have been mixed regarding CSF FAS levels in AD [50] , [51] ; AD plasma/serum VEGF levels have been reported to be unchanged [52] , [53] , decreased [54] , and increased [55] , while CSF levels have been reported to be unchanged [56] or increased [57] ; no change in CSF or serum levels of TNF RII in AD has been reported [58] ; cystatin C findings have been inconsistent, with reports of serum/plasma levels unchanged [59] , increased in AD [60] or in those who later develop AD [61] , and decreased [62] or decreased levels associated with increased risk of future AD [63] , while CSF levels have been reported to be unchanged [59] , [64] , decreased [65] , or increased [21] . These inconsistent results may be due in part to the existence of a truncated form of cystatin C, which was found to be increased in AD CSF, while the full length protein was decreased [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…In regards to L-PGDS, its decrease has been attributed to arachnoidopathy (i.e., loss of arachnoid cells producing L-PGDS) particularly in secondary NPH after subarachnoid hemorrhage [ 13 , 26 ]. In our study, decreased L-PGDS was correlated with a narrow callosal angle, which is a feature of an uneven CSF distribution in DESH-type iNPH.…”
Section: Discussionmentioning
confidence: 99%